KONDISI FINANCIAL DISTRESS PADA EMITEN YANG TERGOLONG DALAM NOTASI KHUSUS BURSA EFEK INDONESIA - Netina Putri Agusta, Patrecia; Dyah Ayu, Stephana (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to describe financial distress and how the ratio of each variable in the Altman Z-Score represents financial distress. This research method is descriptive quantitative, the population of this study is a company that belongs to the special notation of the Indonesian stock exchange for the November 2022 period of 145 issuers, the sampling method uses purposive sampling and 13 issuers are obtained each year. The results of the study show that the majority of issuers from 2019 to 2021 experience financial distress.